A randomized phase 2 study comparing two doses of delafloxacin with tigecycline in adults with complicated skin and skin-structure infections. (January 2015) - O'Riordan, William; Mehra, Purvi; Manos, Paul; Kingsley, Jeff; Lawrence, Laura; Cammarata, Sue
Highlights: Complicated skin and skin-structure infections (cSSSIs) may require surgery. A study of the efficacy and safety of two doses of delafloxacin vs. tigecycline in cSSSIs was performed. Patients were randomized by infection type: abscess, wound infection, or cellulitis. Both delafloxacin and tigecycline had cure rates >90% for all pathogens/infections. Delafloxacin was well tolerated at a dose of 300 mg intravenous every 12 h. Summary: Background: A randomized, double-blind, multicenter trial was done to compare two doses of delafloxacin with tigecycline in patients with various complicated skin and skin-structure infections (wound infections following surgery, trauma, burns, or animal/insect bites, abscesses, and cellulitis). Methods: Patients were randomized 1:1:1 to receive delafloxacin 300 mg intravenous (IV) every 12 h, delafloxacin 450 mg IV every 12 h, or tigecycline 100 mg IV × 1, followed by 50 mg IV every 12 h; randomization was stratified by infection type. Duration of therapy was 5–14 days. The primary efficacy analysis, performed on the clinically evaluable (CE) population at the test-of-cure (TOC) visit (14–21 days after the final dose of study drug), compared clinical response rates in the delafloxacin and tigecycline arms. Clinical response rates in the two delafloxacin arms were also compared. Results: Among CE patients, clinical cure rates at TOC visit were similar in the delafloxacin and tigecycline arms (94.3%, 92.5%, and 91.2%, respectively in delafloxacin 300- mg, delafloxacin 450- mg, and tigecycline arms). Overall, the most frequent adverse events were nausea, vomiting, and diarrhea; the 300-mg delafloxacin arm was the best-tolerated regimen. Conclusions: Delafloxacin was similarly effective as tigecycline for a variety of complicated skin and skin-structure infections and was well tolerated. (Clinicaltrials.gov NCT 0719810)